The limits of political hope in 1988: Jelinek's Wolken.Heim. in context - Morgan, B (Modern Humanities Research Association, 2014)
The article endeavours to return Elfriede Jelinek's first postdramatic play, Wolken.Heim., to the pre-Unification context in which it was conceived. This renders the ambivalence of the play more noticeable and allows the utopian appeal of the Hölderlin poetry cited and re-written by Jelinek to be heard alongside her bleak portrayal of German nationalism. Where Jelinek herself eschews characters, preferring to stage discourse detached from a human speaker, both positive and negative responses to the play have coped with the ambivalence by linking it to specific speakers. The article shows this response in Jossi Wieler's 1993 Hamburg production of the play, and argues that, whilst it situates the ambivalence, the Wieler production shares with Jelinek a distrust of bodily reactions allowing no sense of how to overcome this. A reading of Timberlake Wertenbaker's Our country's good (1988) suggests ways in which the physical encounter of a theatrical performance might itself supply resources for moving beyond the ambivalence set out in Jelinek's text.